Some issues of cyberbullying prevention in the Republic of Kazakhstan - Kalkayeva Н.Б.; Yzbassova А.Б.; Bugybay Д.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The purpose of the article is to form measures to prevent cyberbullying, a common phenomenon today. The article discusses the concept of bullying, including the content of cyberbullying, the system of measures necessary to prevent cyberbullying, and the subjects involved in the prevention of cyberbullying. The methodological basis of the study is the provisions of the sciences of criminology, victimology. The urgency of preventing cyberbullying is associated with the growing use of modern technologies and social networks, which have become an integral part of the lives of many people, especially teenagers and children. Cyberbullying is a form of psychological violence that occurs through the Internet and other digital technologies. Cyberbullying can lead to serious consequences for the victim, such as depression, anxiety, low self-esteem, and in some cases, suicide. Therefore, the prevention of cyberbullying is an important task for society. Prevention of cyberbullying should include teaching children and adolescents to safe behavior on the Internet, establishing rules for the use of social networks and messengers, as well as teaching parents and teachers how to recognize and prevent cases of cyberbullying. For the prevention of cyberbullying, it is also important to create special services that will deal with the prevention and investigation of cases of cyberbullying, as well as provide assistance to victims. The authors of the article state that the prevention of cyberbullying is a necessary measure to ensure the safety of children and adolescents on the Internet. It should be implemented at the level of society, including State organizations, educational institutions and parents.